2019
DOI: 10.1021/acssuschemeng.9b01046
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Molecular Structure of Kraft Lignins—Ozone Treatment at Alkaline Conditions

Abstract: Homogeneous solutions of Kraft lignin can be prepared in alkali. In this environment, ozonean effective and established bleaching agentrapidly converts into a variety of reactive oxygen species, leading to complex oxidation processes. In this study, Kraft lignin was treated with ozone in alkaline solution, and the modified lignin was fractionated into a precipitable, an adsorbable, and a soluble fraction to trace and understand the effects of this treatment. Changing the starting pH showed a distinct effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Therefore, oxidation of oxygen-pretreated lignin with ozone will result in a further increase in the carboxyl content. The ozonation treatment was carried out at ambient pressure in a glass bubbler with a capacity of 1 L. The details of the ozonation procedure are described in the literature . The glass bubbler was heated to 80 °C in a water bath with constant stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, oxidation of oxygen-pretreated lignin with ozone will result in a further increase in the carboxyl content. The ozonation treatment was carried out at ambient pressure in a glass bubbler with a capacity of 1 L. The details of the ozonation procedure are described in the literature . The glass bubbler was heated to 80 °C in a water bath with constant stirring.…”
Section: Methodsmentioning
confidence: 99%
“…The ozonation treatment was carried out at ambient pressure in a glass bubbler with a capacity of 1 L. The details of the ozonation procedure are described in the literature. 38 The glass bubbler was heated to 80 °C in a water bath with constant stirring. A flow of ozone was supplied by a “5G Lab Benchtop Ozone Generator” from A2Z Ozone providing an ozone dosage of 5000 mg h –1 (100% capacity, oxygen flow rate 2 LPM).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, Kraft lignin is mainly used for thermal energy generation . Several reactions have been reported for the depolymerization of lignin, ,, including thermal, biochemical, oxidative, and reductive conversions. , Overall, the degradation reaction mostly suffers from the use of toxic chemicals, reagent waste, harsh reaction conditions, and/or a broad spectrum of cleavage products. A common method for the oxidative Kraft lignin depolymerization to monoaromatic compounds is the use of nitrobenzene under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the in situ formed peracid could be used as the main oxidant. Musl et al 78 treated sulfate lignin in alkaline solution with ozone. During the oxidation process, small molecular organic compounds were produced, resulting in the transfer of main active substances.…”
Section: Oxidationmentioning
confidence: 99%